Organização em sistema caótico: uso das tags para classificação da informação pelos usuários da rede social Twitter - (:unkn) unknown (Universidade Federal do Rio de Janeiro / Instituto Brasileiro de Informação em Ciência e Tecnologia, 2012)
It discusses issues related to classification and knowledge organization, folksonomy, information retrieval and the theories of chaos and complexity in systems, in order to approach the concepts needed to conduct the investigation. Approaches classification since its innate character, through the philosophical studies started in antiquity, even to the scientific approach to design of bibliographic classifications, and the classifications that have been used for organizing information in the Web 2.0 era. The theoretical discussion is developed on the theories of chaos and complexity in systems and their relationship with social networking sites. In particular with the social network Twitter which is a network of messages posted by users of the system, limited to 140 characters, without forming user groups by communities or groups of interest, as it is common in other social networks. The exploratory and empirical research shows the use and purpose of hashtags in Twitter, highlighting the role of collaboration in the choice of terms. Concludes that collaboration is essential to make information retrieval more effective, as well as acting in the convergence of knowledge
Keywords: Classification; Twitter; Knowledge organization; Semantic web; Chaos theory; Classificação; Twitter; Organização do conhecimento; Web semântica; Teoria do caos; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO